Gender and Workplace Equity: Exploring Gender Equity and Workplace Diversity: Challenges and Opportunities (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper focuses on the employment Equity and its various related sub-issues like the glass ceiling, men’s Dominance in the organization, target group, government policies, and quotas system. This paper answers the questions like “Is workplace equity is just a buzz word to justify reverse discrimination?” and “Aren’t we overlooking women’s shortcoming because of organization’s commitment to promoting women?” So workplace equity is a concern with advancement which solely balanced with merit and a skill, Moreover actively promotes the deserving women and minorities group without any partiality and discrimination of any kind. Perfect workplace equity makes an organization an ideal place to work on and improve the socially responsible image of the organization.